2017
DOI: 10.1016/j.jsxm.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Physical Tenderness in Older Adults: Cross-Sectional Prevalence and Associated Characteristics

Abstract: Background Despite a common misconception, older adults engage in sexual behavior. However, there is limited sexual behavior research in older adults, which is often restricted to small samples, to cohorts recruiting adults from 45 years old, and to questions regarding only sexual intercourse. Aim To assess the cross-sectional prevalence of and characteristics associated with sexual activity and physical tenderness in communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 36 publications
1
70
1
Order By: Relevance
“…Secondly, studies have suggested that for many older adults, physical closeness and intimacy may be more important than sexual activity per se (Sandberg 2013;Müller et al 2014;Lee et al 2016;Fileborn et al 2017;Freak-Poli et al 2017). Based on findings from a large study of midlife and older adults' definitions of sexual wellness, Symes et al (2018) concluded that conceptualizing and measuring sexual wellness in this population requires a multidimensional approach that includes psychological, social, and attitudinal aspects in addition to sexual function and activity-related ones.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, studies have suggested that for many older adults, physical closeness and intimacy may be more important than sexual activity per se (Sandberg 2013;Müller et al 2014;Lee et al 2016;Fileborn et al 2017;Freak-Poli et al 2017). Based on findings from a large study of midlife and older adults' definitions of sexual wellness, Symes et al (2018) concluded that conceptualizing and measuring sexual wellness in this population requires a multidimensional approach that includes psychological, social, and attitudinal aspects in addition to sexual function and activity-related ones.…”
Section: Introductionmentioning
confidence: 99%
“…In the past year, 30.4% had given or received oral sex and 2.9% had had anal sex with a female partner (Mercer et al 2013). While cultural factors and social mores shape sexual attitudes and behaviours (McLaren 2005), similar results about the sexual activity of older adults have been reported in the USA (Herbenick et al 2010), Australia (Heywood et al 2018), the Netherlands (Freak-Poli et al 2017), and Spain (Palacios-Ceña et al 2012). These findings indicate similairity in the levels of sexual activity of older adults, potentially on a global scale.…”
Section: Sexual Activity and Sexual Difficultiesmentioning
confidence: 83%
“…A substantial body of research indicates that the majority of older adults are sexually active and enjoy a range of sexual activities (DeLamater and Koepsel 2015;Fileborn et al 2015;Freak-Poli et al 2017). Sexual activity and intimacy have been found to contribute to the quality of life of older women and men in countries across the world (see Traeen et al 2017a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual activity Almost half of partnered older adults engage in sexual activity and over two-thirds engage in physical tenderness, but very few unpartnered older adults engage in sexual behaviour [ 345 ]. The greatest barrier to being sexually active at older age is lack of sexual partner availability, for which women are particularly disadvantaged.…”
Section: Psychiatric Epidemiologymentioning
confidence: 99%